If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9c + -36 = 0 Reorder the terms: -36 + 9c = 0 Solving -36 + 9c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 9c = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 9c = 0 + 36 9c = 0 + 36 Combine like terms: 0 + 36 = 36 9c = 36 Divide each side by '9'. c = 4 Simplifying c = 4
| (x+y)dx+(x-y)dy=0 | | 7(5-4)+3x=4(x+2) | | -13-7x=9x-11 | | 12x+7=-4x+9 | | -15=-5y | | 8x+4/2=4x-2/3 | | 15/3-7x=9+5x | | 27-6d=7+4 | | 57/9+48/9 | | 15-10=6x-(x+2)+(-x+3) | | (4x-1)-(x-3)= | | .33a-.75=6 | | (x+2)(x-3)=(x+3)3 | | 3x-2=5(1-9x^2)^1/2 | | 2n+8=-32 | | (3x-11)+(-4+1)= | | 10^5x10^-7/10^2 | | -3x-2x-10=10 | | -9(v+3)=-2v+15 | | a+a+a/3+2=100 | | 6x-(4x+9)=5x-36 | | 6x^2+10xy-4x^2=0 | | 2x^3-7x^2+2x+3=0 | | 234x^2-12x-24=0 | | 4(6y-5)=23-3(8y+1) | | 6x^2+8x-9.5=0 | | -x+16x-2=0 | | 10/40-20x | | y=x*2-4x-12 | | n+2/3=35 | | 48y^3-3u^4y^3=0 | | 9=u/5-9 |